WSB1, as an E3 ligase, restrains myocardial ischemia-reperfusion injury by activating β-catenin signaling via promoting GSK3β ubiquitination - Lini Fang; Yang Tao; Guoying Che; Yongzi Yun; Min Ren; Yujie Liu (BMC, 2024)
Abstract Background Reperfusion is the most effective strategy for myocardial infarct, but induces additional injury. WD repeat and SOCS box containing protein 1 (WSB1) plays a protective role in ischemic cells. This study aims to investigate the effects of WSB1 on myocardial ischemia-reperfusion (IR) injury. Methods The myocardial IR was induced by left anterior descending (LAD) ligation for 45 min and subsequent reperfusion. The overexpression of WSB1 was mediated by tail vein injection of AAV9 loaded with WSB1 encoding sequence two weeks before IR surgery. H9c2 myocardial cells underwent oxygen-sugar deprivation/reperfusion (OGD/R) to mimic IR, and transfected with WSB1 overexpression or silencing plasmid to alter the expression of WSB1. Results WSB1 was found highly expressed in penumbra of myocardial IR rats, and the WSB1 overexpression relieved IR-induced cardio dysfunction, myocardial infarct and pathological damage, and cardiomyocyte death in penumbra. The ectopic expression of WSB1 in H9c2 myocardial cells mitigated OGD/R-caused apoptosis, and silencing of WSB1 exacerbated the apoptosis. In addition, WSB1 activated β-catenin signaling, which was deactivated under the ischemic condition. The co-immunoprecipitation results revealed that WSB1 mediated ubiquitination and degradation of glycogen synthase kinase 3 beta (GSK3β) as an E3 ligase in myocardial cells. The effects of WSB1 on myocardial cells under ischemic conditions were abolished by an inhibitor of β-catenin signaling. Conclusion WSB1 activated β-catenin pathway by promoting the ubiquitination of GSK3β, and restrained IR-induced myocardial injury. These findings might provide novel insights for clinical treatment of myocardial ischemic patients.